Skill mismatch in labor markets - Polachek, S. W.; Tatsiramos, Konstantinos; Pouliakas, Konstantinos; Russo, Giovanni, active 2017 (Research in labor economics ;, 2017)
The 2008 global financial and economic crisis led to a significant increase in unemployment rates in most developed economies, yet despite the rising supply of labor, a high share of employers claim that they cannot find the right talent and skills. Concerns that economic restructuring and changing skill needs associated with new technologies and workplace organization practices will not be met by an adequately skilled workforce, has placed the issue of skill mismatch - the incongruence between skill supply and skill demand - high up in the policy agenda. This volume contains eleven original research articles which deal with the linkages between education and skills and the causes and consequences of different types of skill mismatch. Topics include the way graduate jobs can be defined, the labor market decisions and outcomes of graduates, the determinants of the overeducation wage penalty, the determinants and consequences of underskilling, the wage return of skills, the impact of skill mismatch on aggregate productivity, and the role of work-related training and job complexity on skill development.